Enhancing vineyard soil mycorrhizal properties and grape and wine phenolic profiles through microbial inoculation and interrow green cover - Gergely Ujvári; Agnese Bellabarba; Silvia Mangani; Matteo Daghio; Viola Galli; Lisa Granchi; Monica Agnolucci; Alessandra Turrini; Luciano Avio; Giacomo Buscioni; Manuela Giovannetti; Simona Guerrini; et al. (Applied Soil Ecology, 2026)

Floor vegetation management affects diversity and composition of mycorrhizal symbionts and soil microbial communities in a Mediterranean olive orchard - Arianna GRASSI; Irene PAGLIARANI; Eleonora GRANATA; Luciano AVIO; Caterina CRISTANI; Flavia MASCAGNI; Manuela GIOVANNETTI; Chiara PICCINI; Claudio CANTINI; Alessandra TURRINI; Monica AGNOLUCCI (Pedosphere, 2026)

Bacteria associated with spores of arbuscular mycorrhizal fungi: a review - Monica Agnolucci; Arianna Grassi; Manuela Giovannetti; Olga A. Lastovetsky (Biology and Fertility of Soils, 2026)
Arbuscular mycorrhizal fungi (AMF) are important components of terrestrial ecosystems and sustainable agricultural practices, forming mutually beneficial symbiotic associations with roots of most land plants including crops by providing them with nutrients in exchange for photosynthesis-derived carbon and protection from biotic and abiotic stresses. Microorganisms, including bacteria, are emerging as important new players in the AMF-plant symbiosis by influencing symbiotic outcome. Specifically, bacteria can tightly associate with AMF extraradical mycelium and spores. Spores are produced mainly in the soil and function in reproduction and dissemination. Spores are large and full of lipids and therefore represent an important soil carbon pool as well as an attractive niche for soil bacteria, termed the “sporosphere”. Intriguingly, diverse bacterial communities have been found in different parts of the sporosphere environment, and they may possess roles in complementing and enhancing AMF function. In this review, we describe the AMF sporosphere environment and summarize our current knowledge of spore-associated bacterial communities including their composition, assembly, function and localization. We also identify knowledge gaps and future research directions as well as highlight spores as model systems for studying AMF–microbe interactions.

Complementary functionalities of extracellular polymeric substances, adhesion ability and hydrophobicity in Pseudomonas isolates may help the selection of strategically advantageous microbial inoculants - Federico Rossi; Arianna Grassi; Caterina Cristani; Irene Pagliarani; Manuela Giovannetti; Monica Agnolucci (World Journal of Microbiology and Biotechnology, 2026)

Root endophytic bacterial communities are shaped by the specific microbiota associated to mycorrhizal symbionts - Gergely Ujvári; Arianna Grassi; Luciano Avio; Irene Pagliarani; Caterina Cristani; Manuela Giovannetti; Monica Agnolucci; Alessandra Turrini (Plant and Soil, 2025)
Background and aims Arbuscular mycorrhizal fungi (AMF) are beneficial soil microorganisms establishing mutualistic symbioses with most crop plants and promoting plant growth and health. AMF beneficial activities are complemented by their associated microbiota, leading to synergistic interactions positively affecting plant performance. In this work we assessed whether AMF may act as drivers of root bacterial endophytes, facilitating root colonization of host plants by their associated bacteria. Methods Two AMF isolates were used, Funneliformis mosseae from Indiana (USA) and Septoglomus sp. from Tuscany (Italy) in an original experimental microcosm system, utilizing micropropagated plants of Prunus persica x Prunus amygdalus inoculated with either intact or mechanically crushed AMF spores, the former able and the latter unable to establish the symbiosis. Spore and root endophytic bacterial communities diversity were analysed by Illumina Miseq sequencing. Results This study revealed that AMF with their associated bacteria can shape the root endophytic bacterial communities, inducing differential recruitment depending on the composition of spore-associated microbiota. Such data were consistent between two AMF isolates, associated with diverse bacterial communities, as shown by PERMANOVA, Bray Curtis dissimilarity, hierarchical clustering and indicator species analyses. Moreover, specific bacterial taxa were found exclusively in mycorrhizal roots. Our findings suggested also a differential recruitment depending on the ability of AMF to establish mycorrhizal symbioses. Conclusion This work revealed that AMF represent drivers of the endophytic bacterial communities diversity and composition, facilitating root colonization of host plants by their associated bacteria, that become an integral part of the root microbiome as endophytes.

Correction: Agricultural Managements Influence the Diversity of Arbuscular Mycorrhizal Fungi in Vineyards from Chilean Mediterranean Climate Ecosystems - Ana Aguilar-Paredes; Alessandra Turrini; Luciano Avio; Cristian Stuardo; Alexis Velásquez; José Becerra; Manuela Giovannetti; Michael Seeger (Journal of Soil Science and Plant Nutrition, 2024)

Agricultural Managements Influence the Diversity of Arbuscular Mycorrhizal Fungi in Vineyards from Chilean Mediterranean Climate Ecosystems - Ana Aguilar-Paredes; Alessandra Turrini; Luciano Avio; Cristian Stuardo; Alexis Velásquez; José Becerra; Manuela Giovannetti; Michael Seeger (Journal of Soil Science and Plant Nutrition, 2024)
Purpose Grapevine ( Vitis vinifera L.) is a relevant crop, which is associated to arbuscular mycorrhizal fungi (AMF) that are influenced by agricultural practices. The hypothesis of this study is that organic/biodynamic management stimulates grapevine mycorrhizal colonisation and increases AMF diversity in Chilean vineyards. The aim of this study was to determine the influence of agricultural management on AMF association and AMF diversity in Chilean vineyards. Methods Mycorrhizal colonisation of grapevine roots from organic/biodynamic and conventional vineyards in Northern (Elqui Valley), Central (Casablanca and Cachapoal Valleys), and Southern Chile (Maule and Itata Valleys), was determined under a microscope. AMF diversity was analysed by morphological, and molecular characterisation of spores through SSU-ITS-LSU rRNA region sequence analyses. Results AMF colonisation of grapevine roots was influenced by vineyard management independent of the season. Higher mycorrhizal colonisation was detected in organic/biodynamic grapevine soils (20 − 35%), compared with conventional soils (6 − 31%). Twelve AMF species were identified in vineyards, belonging to five Glomeromycota families. Interestingly, organic/biodynamic vineyards showed higher AMF diversity. The three predominant morphotypes were Funneliformis verruculosum (GL1) , Septoglomus sp. (GL4) and Septoglomus constrictum (GL5). Molecular analyses of AMF spores highlighted the occurrence of Septoglomus, Acaulospora, Pacispora and Cetraspora genera in vineyards. Conclusions In this study, AMF diversity in Chilean vineyards is described for the first time. The diversity of AMF in vineyards in Chile was higher than the diversity reported in other wine-producing ecosystems. The understanding of agricultural practices on AMF activity and diversity may be crucial to improve the vineyard management.

Bioprospecting for plant resilience to climate change: mycorrhizal symbionts of European and American beachgrass (Ammophila arenaria and Ammophila breviligulata) from maritime sand dunes - Arianna Grassi; Irene Pagliarani; Luciano Avio; Caterina Cristani; Federico Rossi; Alessandra Turrini; Manuela Giovannetti; Monica Agnolucci (Mycorrhiza, 2024)
Climate change and global warming have contributed to increase terrestrial drought, causing negative impacts on agricultural production. Drought stress may be addressed using novel agronomic practices and beneficial soil microorganisms, such as arbuscular mycorrhizal fungi (AMF), able to enhance plant use efficiency of soil resources and water and increase plant antioxidant defence systems. Specific traits functional to plant resilience improvement in dry conditions could have developed in AMF growing in association with xerophytic plants in maritime sand dunes, a drought-stressed and low-fertility environment. The most studied of such plants are European beachgrass ( Ammophila arenaria Link), native to Europe and the Mediterranean basin, and American beachgrass ( Ammophila breviligulata Fern.), found in North America. Given the critical role of AMF for the survival of these beachgrasses, knowledge of the composition of AMF communities colonizing their roots and rhizospheres and their distribution worldwide is fundamental for the location and isolation of native AMF as potential candidates to be tested for promoting crop growth and resilience under climate change. This review provides quantitative and qualitative data on the occurrence of AMF communities of A. arenaria and A. breviligulata growing in European, Mediterranean basin and North American maritime sand dunes, as detected by morphological studies, trap culture isolation and molecular methods, and reports on their symbiotic performance. Moreover, the review indicates the dominant AMF species associated with the two Ammophila species and the common species to be further studied to assess possible specific traits increasing their host plants resilience toward drought stress under climate change.

Native mycorrhizal communities in maize roots as affected by plant genotype, starter fertilization and a seed-applied biostimulant - Gergely Ujvári; Arianna Grassi; Caterina Cristani; Irene Pagliarani; Luciano Avio; Massimo Blandino; Luca Capo; Manuela Giovannetti; Alessandra Turrini; Monica Agnolucci (Plant and Soil, 2023)
Background and aims One of the most promising strategies for sustainable intensification of crop production involves the utilization of beneficial root-associated microorganisms, such as plant growth-promoting bacteria and arbuscular mycorrhizal fungi (AMF). The aim of this study was to investigate whether a seed-applied biostimulant, based on the bacterial strain Bacillus amyloliquefaciens IT-45 and a plant polysaccharide extract, and crop enhancement tools, such as hybrids with contrasting early vigor and nitrogen (N) plus phosphorus (P) starter fertilization, and their interactions, shape the communities of native root-colonizing AMF symbionts in maize. Methods A factorial growth chamber experiment was set up with two maize genotypes in natural soil. Mycorrhizal colonization was evaluated after root staining. The diversity and composition of AMF communities were assessed by PCR-DGGE of the 18S rRNA gene and amplicon sequencing. Results N and P fertilization determined a consistent reduction of AMF root colonization and, in combination of biostimulant, a reduction of AMF richness. The biostimulant alone generally did not affect AMF colonization or the community biodiversity. In addition the effect of the two factors were modulated by maize genotype. In all treatments, predominant AMF were represented by Glomus sp. and Funneliformis mosseae , while populations of the genus Rhizoglomus were rarely detected in biostimulant and NP fertilization treatments. Conclusion The results of this study increase our understanding of how the biostimulant seed treatment may affect native AMF communities, depending on NP fertilization and maize genotype and may improve the implementation of innovative tools in sustainable and resilient agroecosystems.

Effects of pavements on diversity and activity of mycorrhizal symbionts associated with urban trees - Arianna Grassi; Irene Pagliarani; Caterina Cristani; Michela Palla; Alessio Fini; Sebastien Comin; Piero Frangi; Manuela Giovannetti; Alessandra Turrini; Monica Agnolucci (Urban Forestry & Urban Greening, 2023)

Do changes in Lactuca sativa metabolic performance, induced by mycorrhizal symbionts and leaf UV-B irradiation, play a role towards tolerance to a polyphagous insect pest? - Marco Santin; Valeria Zeni; Arianna Grassi; Renato Ricciardi; Ylenia Pieracci; Filippo Di Giovanni; Sofia Panzani; Christian Frasconi; Monica Agnolucci; Luciano Avio; Alessandra Turrini; Manuela Giovannetti; et al. (Environmental Science and Pollution Research, 2023)
The increased ultraviolet radiation (UV) due to the altered stratospheric ozone leads to multiple plant physiological and biochemical adaptations, likely affecting their interaction with other organisms, such as pests and pathogens. Arbuscular mycorrhizal fungi (AMF) and UV-B treatment can be used as eco-friendly techniques to protect crops from pests by activating plant mechanisms of resistance. In this study, we investigated plant ( Lactuca sativa ) response to UV-B exposure and Funneliformis mosseae (IMA1) inoculation as well as the role of a major insect pest, Spodoptera littoralis . Lettuce plants exposed to UV-B were heavier and taller than non-irradiated ones. A considerable enrichment in phenolic, flavonoid, anthocyanin, and carotenoid contents and antioxidant capacity, along with redder and more homogenous leaf color, were also observed in UV-B-treated but not in AMF-inoculated plants. Biometric and biochemical data did not differ between AMF and non-AMF plants. AMF-inoculated plants showed hyphae, arbuscules, vesicles, and spores in their roots. AMF colonization levels were not affected by UV-B irradiation. No changes in S. littoralis -feeding behavior towards treated and untreated plants were observed, suggesting the ability of this generalist herbivore to overcome the plant chemical defenses boosted by UV-B exposure. The results of this multi-factorial study shed light on how polyphagous insect pests can cope with multiple plant physiological and biochemical adaptations following biotic and abiotic preconditioning.

Zinc and Iron Biofortification and Accumulation of Health-Promoting Compounds in Mycorrhizal Cichorium intybus L. - Alessandra Pepe; Daniela Di Baccio; Ermenegildo Magnani; Manuela Giovannetti; Cristiana Sbrana (Journal of Soil Science and Plant Nutrition, 2022)
The positive impact of arbuscular mycorrhizal symbionts on plant growth and health has been reported for many species, and supports their use as biofertilizers and bioenhancers. Here, the potential role of the arbuscular mycorrhizal symbiont Funneliformis mosseae in the improvement of chicory ( Cichorium intybus L.) nutritional value, in terms of nutrient uptake and accumulation of health-promoting compounds, was studied using an in vivo whole-plant system, allowing both plant and fungal tissue collection. Biomass and nutrient distribution were determined in plant and extraradical mycelium, and photosynthetic pigments and fructooligosaccharide concentrations were evaluated in chicory shoots and roots. Zinc shoot concentration of mycorrhizal chicory was significantly increased, as well as the whole-plant Fe uptake, while root Cu concentration was decreased, compared with uninoculated controls. F. mosseae extraradical mycelium accumulated Cu, Zn, Mn, and Fe at high concentrations, compared with those of the host plant tissues, suggesting that it plays a double functional “scavenging-filtering” role, by its ability to balance the uptake of microelements or to limit their translocation depending on plant-soil concentrations. The higher Zn and Fe uptake by mycorrhizal plants was significantly correlated with higher carotenoid, inulin, and fructose levels, suggesting a relationship among the modulation of micronutrient uptake by mycorrhizal symbionts and the biosynthesis of health-promoting molecules by the host. Overall, data from this work may boost the implementation of arbuscular mycorrhizal fungal inoculation aimed at inducing plant biofortification and enhancement of nutritional value of plant-derived food.

Appressoria and phosphorus fluxes in mycorrhizal plants: connections between soil- and plant-based hyphae - Alessandra Pepe; Manuela Giovannetti; Cristiana Sbrana (Mycorrhiza, 2020)

Gene expression in Rhizoglomus irregulare at two different time points of mycorrhiza establishment in Helianthus annuus roots, as revealed by RNA-seq analysis - Alberto Vangelisti; Alessandra Turrini; Cristiana Sbrana; Luciano Avio; Tommaso Giordani; Lucia Natali; Manuela Giovannetti; Andrea Cavallini (Mycorrhiza, 2020)

Mycorrhizal networks facilitate the colonization of legume roots by a symbiotic nitrogen-fixing bacterium - Candido Barreto de Novais; Cristiana Sbrana; Ederson da Conceição Jesus; Luc Felicianus Marie Rouws; Manuela Giovannetti; Luciano Avio; José Oswaldo Siqueira; Orivaldo José Saggin Júnior; Eliane Maria Ribeiro da Silva; Sergio Miana de Faria (Mycorrhiza, 2020)

Responses of Vitis vinifera cv. Cabernet Sauvignon roots to the arbuscular mycorrhizal fungus Funneliformis mosseae and the plant growth-promoting rhizobacterium Ensifer meliloti include changes in volatile organic compounds - Alexis Velásquez; Paulina Vega-Celedón; Grazia Fiaschi; Monica Agnolucci; Luciano Avio; Manuela Giovannetti; Claudio D’Onofrio; Michael Seeger (Mycorrhiza, 2020)

Two herbicides, two fungicides and spore-associated bacteria affect Funneliformis mosseae extraradical mycelium structural traits and viability - Candido Barreto de Novais; Manuela Giovannetti; Sergio Miana de Faria; Cristiana Sbrana (Mycorrhiza, 2019)

Atmospheric nitrogen fixation by gliricidia trees (Gliricidia sepium (Jacq.) Kunth ex Walp.) intercropped with cocoa (Theobroma cacao L.) - James Seutra Kaba; Stefan Zerbe; Monica Agnolucci; Francesca Scandellari; Akwasi A. Abunyewa; Manuela Giovannetti; Massimo Tagliavini (Plant and Soil, 2019)

Rhizoglomus venetianum, a new arbuscular mycorrhizal fungal species from a heavy metal-contaminated site, downtown Venice in Italy - Alessandra Turrini; Martina Saran; Manuela Giovannetti; Fritz Oehl (Mycological Progress, 2018)

Quorum sensing in rhizobia isolated from the spores of the mycorrhizal symbiont Rhizophagus intraradices - Michela Palla; Fabio Battini; Caterina Cristani; Manuela Giovannetti; Andrea Squartini; Monica Agnolucci (Mycorrhiza, 2018)

Divergence of Funneliformis mosseae populations over 20 years of laboratory cultivation, as revealed by vegetative incompatibility and molecular analysis - Cristiana Sbrana; Patrizia Strani; Alessandra Pepe; Candido Barreto de Novais; Manuela Giovannetti (Mycorrhiza, 2018)

Local diversity of native arbuscular mycorrhizal symbionts differentially affects growth and nutrition of three crop plant species - Alessandra Turrini; Alberico Bedini; Mario Bonilla Loor; Gaia Santini; Cristiana Sbrana; Manuela Giovannetti; Luciano Avio (Biology and Fertility of Soils, 2018)

An in vivo whole-plant experimental system for the analysis of gene expression in extraradical mycorrhizal mycelium - Alessandra Pepe; Cristiana Sbrana; Nuria Ferrol; Manuela Giovannetti (Mycorrhiza, 2017)

Rhizophagus intraradices or its associated bacteria affect gene expression of key enzymes involved in the rosmarinic acid biosynthetic pathway of basil - Fabio Battini; Rodolfo Bernardi; Alessandra Turrini; Monica Agnolucci; Manuela Giovannetti (Mycorrhiza, 2016)

Changes in the composition of native root arbuscular mycorrhizal fungal communities during a short-term cover crop-maize succession - Alessandra Turrini; Cristiana Sbrana; Luciano Avio; Ezekiel Mugendi Njeru; Gionata Bocci; Paolo Bàrberi; Manuela Giovannetti (Biology and Fertility of Soils, 2016)

Different levels of hyphal self-incompatibility modulate interconnectedness of mycorrhizal networks in three arbuscular mycorrhizal fungi within the Glomeraceae - Alessandra Pepe; Manuela Giovannetti; Cristiana Sbrana (Mycorrhiza, 2016)

The rat glucocorticoid receptor integration in Nicotiana langsdorffii genome affects plant responses to abiotic stresses and to arbuscular mycorrhizal symbiosis - Patrizia Bogani; Elisa Calistri; Stefano Biricolti; Monica Ruffini Castiglione; Alessandra Turrini; Manuela Giovannetti; Marcello Buiatti (Plant Biotechnology Reports, 2015)

Diverse bacterial communities are recruited on spores of different arbuscular mycorrhizal fungal isolates - Monica Agnolucci; Fabio Battini; Caterina Cristani; Manuela Giovannetti (Biology and Fertility of Soils, 2015)

Contrasting effects of cover crops on ‘hot spot’ arbuscular mycorrhizal fungal communities in organic tomato - Ezekiel Mugendi Njeru; Luciano Avio; Gionata Bocci; Cristiana Sbrana; Alessandra Turrini; Paolo Bàrberi; Manuela Giovannetti; Fritz Oehl (Biology and Fertility of Soils, 2015)

Mycorrhizal activity and diversity in a long-term organic Mediterranean agroecosystem - Stefano Bedini; Luciano Avio; Cristiana Sbrana; Alessandra Turrini; Paola Migliorini; Concetta Vazzana; Manuela Giovannetti (Biology and Fertility of Soils, 2013)

Vegetative compatibility and anastomosis formation within and among individual germlings of tropical isolates of arbuscular mycorrhizal fungi (Glomeromycota) - Cândido Barreto de Novais; Cristiana Sbrana; Orivaldo José Saggin Júnior; José Oswaldo Siqueira; Manuela Giovannetti (Mycorrhiza, 2013)

Janusz Błaszkowski (ed); Glomeromycota - Manuela Giovannetti (Mycorrhiza, 2013)

Arbuscular mycorrhizal fungi shift competitive relationships among crop and weed species - Hideliza Daisog; Cristiana Sbrana; Caterina Cristani; Anna-Camilla Moonen; Manuela Giovannetti; Paolo Bàrberi (Plant and Soil, 2012)

Fungal biomass production in response to elevated atmospheric CO2 in a Glomus mosseae–Prunus cerasifera model system - Paola Fortuna; Luciano Avio; Stefano Morini; Manuela Giovannetti (Mycological Progress, 2012)

Arbuscular mycorrhizal fungi in national parks, nature reserves and protected areas worldwide: a strategic perspective for their in situ conservation - Alessandra Turrini; Manuela Giovannetti (Mycorrhiza, 2012)

Mycorrhizal colonization impacts on phenolic content and antioxidant properties of artichoke leaves and flower heads two years after field transplant - Nello Ceccarelli; Maurizio Curadi; Luca Martelloni; Cristiana Sbrana; Piero Picciarelli; Manuela Giovannetti (Plant and Soil, 2010)

Mycorrhizal fungi suppress aggressive agricultural weeds - Valeria Rinaudo; Paolo Bàrberi; Manuela Giovannetti; Marcel G. A. van der Heijden (Plant and Soil, 2010)

Arbuscular mycorrhizal fungi of a Mediterranean island (Pianosa), within a UNESCO Biosphere Reserve - Alessandra Turrini; Cristiana Sbrana; Patrizia Strani; Beatrice Pezzarossa; Rosalba Risaliti; Manuela Giovannetti (Biology and Fertility of Soils, 2010)

In situ collection of endangered arbuscular mychorrhizal fungi in a Mediterranean UNESCO Biosphere Reserve - Alessandra Turrini; Luciano Avio; Stefano Bedini; Manuela Giovannetti (Biodiversity and Conservation, 2008)

Self-anastomosing ability and vegetative incompatibility of Tuber borchii isolates - Cristiana Sbrana; Marco P. Nuti; Manuela Giovannetti (Mycorrhiza, 2007)

Development of a model system to assess the impact of genetically modified corn and aubergine plants on arbuscular mycorrhizal fungi - Alessandra Turrini; Cristiana Sbrana; Marco Paolo Nuti; Bianca Maria Pietrangeli; Manuela Giovannetti (Plant and Soil, 2005)

Type of mycorrhizal associations in two coastal nature reserves of the Mediterranean basin - Andrea Maremmani; Stefano Bedini; Ivica Matoševic; Paolo E. Tomei; Manuela Giovannetti (Mycorrhiza, 2003)

Microchambers and video-enhanced light microscopy for monitoring cellular events in living hyphae of arbuscular mycorrhizal fungi - Manuela Giovannetti; Cristiana Sbrana; Cable Logi (Plant and Soil, 2000)